Biodegradation of plastic monomer 2, 6-dimethylphenol by Mycobacterium neoaurum B5-4. (March 2020) - Ji, Junbin; Zhang, Yanting; Liu, Yongchuang; Zhu, Pingping; Yan, Xin
Abstract: 2, 6-Dimethylphenol (2, 6-DMP), an important chemical intermediate and the monomer of plastic polyphenylene oxide, is widely used in chemical and plastics industry. However, the pollution problem of 2, 6-DMP residues is becoming increasingly serious, which is harmful to some aquatic animals. Microbial degradation provided an effective approach to eliminate DMPs in nature, which is considered as a prospective way to remediate DMPs-contaminated environments. But the 2, 6-DMP-degrading bacteria is not available and the molecular mechanism of 2, 6-DMP degradation is unclear as well. Here, a 2, 6-DMP-degrading bacterium named B5-4 was isolated and identified as Mycobacterium neoaurum . M. neoaurum B5-4 could utilize 2, 6-DMP as the sole carbon source for growth. Furthermore, M. neoaurum B5-4 could degrade 2, 6-DMP with concentrations ranging from 1 to 500 mg L −1 . Six intermediate metabolites of 2, 6-DMP were identified and a metabolic pathway of 2, 6-DMP in M. neoaurum B5-4 was proposed, in which 2, 6-DMP was initially converted to 2, 6-dimethyl-hydroquinone and 2, 6-dimethyl-3-hydroxy-hydroquinone by two consecutive hydroxylations at C-4 and γ position; 2, 6-dimethyl-3-hydroxy-hydroquinone was then subjected to aromatic ring ortho- cleavage to produce 2, 4-dimethyl-3-hydroxymuconic acid, which was further transformed to citraconate, and subsequently into TCA cycle. In addition, toxicity bioassay of 2, 6-DMP in water using zebrafish indicates that 2, 6-DMP is toxic to zebrafish and M. neoaurum B5-4 could effectively eliminate 2, 6-DMP in water to protect zebrafish from 2, 6-DMP-induced death. This work provides a potential strain for bioremediation of 2, 6-DMP-contaminated environments and lays a foundation for elucidating the molecular mechanism and genetic determinants of 2, 6-DMP degradation. Graphical abstract: Image 1 Highlights: A Mycobacterium neoaurum B5-4 capable of degrading 2, 6-DMP was isolated. Six intermediate metabolites of 2, 6-DMP were identified. A metabolic pathway of 2, 6-DMP in strain B5-4 was proposed. 2, 6-DMP is toxic to zebrafish. Strain B5-4 could effectively eliminate 2, 6-DMP in water to protect zebrafish from 2, 6-DMP-induced death.